‘Sorry, I Don’t Want Them Here.’ Migration in Slovak Political Discourse - R. Štefančík; A. Kiner (Дискурс профессиональной коммуникации, 2021)
The issue of international migration in Slovakia was not a topic of public discussion until 2015. A major change in migration discourse can be observed only after the mass migratory processes in 2015, a few weeks before the Slovak parliamentary elections. Just before the elections, politicians had also noticed these processes, putting the spotlight on migration, which became a frequent priority topic of electoral campaigns for several weeks. Our aim with this paper is to answer a question of how Slovak politicians, who had ignored this topic for many years, dealt with the issue of international migration since 2015 and which aspect dominated the emerging migration discourse. We came to the conclusion that Slovak politicians tackled the issue almost uniformly, regardless of their ideological beliefs or coalition-opposition framework. Most politicians presented migration as a threat. In addition to the securitization of migration discourse, we also observe a gradual shift in the understanding of the term migrant. Until 2015, the naming of the particular actor of migration processes was generally understood to be neutral, yet since 2015 the term has acquired a strong negative connotation.